2021
DOI: 10.1016/j.meegid.2021.105088
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 B.1.1.7 lineage rapidly spreads and replaces R.1 lineage in Japan: Serial and stationary observation in a community

Abstract: Background The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) circulates in the world and acquires mutations during evolution. To identify the new emergent variants, the surveillance of the variants of concern (VOC) and variants of interest (VOI) is ongoing. This study aimed to determine how the transition of viral lineage occurred by stationary genome analysis in Yamanashi, Japan. Methods We performed the whole genome sequencing using SARS-CoV-2 positive … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 32 publications
0
20
0
Order By: Relevance
“…To delineate the possible origin of the five SARS-CoV-2 sequences identified in this study, real-time sequence placement for the SARS-CoV-2 pandemic was performed using an existing phylogenetic tree generated by the sarscov2phylo pipeline, which contains 6,624,590 genomes from GISAID, GenBank, COG-UK, and CNCB. The phylogenetic subtree results suggest that KMUH-3 is closest to ∼200 SARS-CoV-2 sequences collected in Japan during their alpha/B.1.1.7 outbreak ( 59 , 60 ) and that KMUH-4 to KMUH-7 are closest to several SARS-CoV-2 sequences collected in Taiwan during the largest alpha/B.1.1.7 outbreak ( 61 ). Patient number 32 (KMUH-3) had a traveling history to Japan before diagnosed of COVID-19 and patients number 36, 37, 38, and 41 (KMUH-4 to 7) had no traveling history abroad.…”
Section: Discussionmentioning
confidence: 91%
“…To delineate the possible origin of the five SARS-CoV-2 sequences identified in this study, real-time sequence placement for the SARS-CoV-2 pandemic was performed using an existing phylogenetic tree generated by the sarscov2phylo pipeline, which contains 6,624,590 genomes from GISAID, GenBank, COG-UK, and CNCB. The phylogenetic subtree results suggest that KMUH-3 is closest to ∼200 SARS-CoV-2 sequences collected in Japan during their alpha/B.1.1.7 outbreak ( 59 , 60 ) and that KMUH-4 to KMUH-7 are closest to several SARS-CoV-2 sequences collected in Taiwan during the largest alpha/B.1.1.7 outbreak ( 61 ). Patient number 32 (KMUH-3) had a traveling history to Japan before diagnosed of COVID-19 and patients number 36, 37, 38, and 41 (KMUH-4 to 7) had no traveling history abroad.…”
Section: Discussionmentioning
confidence: 91%
“…Whole genome sequencing analysis was conducted in accordance with a previously described method on 489 nasopharyngeal swabs collected from patients with coronavirus disease 2019 (COVID-19) from September 2021 to March 2022. In brief, SARS-CoV-2 genomic RNA was reverse-transcribed into cDNA and amplified using the Ion AmpliSeq SARS-CoV-2 Research Panel or Ion AmpliSeq SARS-CoV-2 Insight Research Assay (Thermo Fisher Scientific, Waltham, MA, USA) on the Ion Torrent Genexus System in accordance with the manufacturer’s instructions [17-19]. Sequencing reads were processed, and their quality was assessed using Genexus Software with SARS-CoV-2 plugins.…”
Section: Methodsmentioning
confidence: 99%
“…Although B.1.1.7, P.1, and B.1.351 had already detected in Japan at the end of December 2020, only B.1.1.7 had spread in Japan and it rapidly increased from February 2021 ( 34 , 35 ). A local surveillance in Japan also suggested that the B.1.1.7 became dominant after mid-April ( 36 ). These observations suggested that all participants in this study were likely to be infected with D614G.…”
Section: Discussionmentioning
confidence: 99%